Autonomic symptoms following Zika virus infection (2018)
Purpose: To determine if autonomic symptoms are associated with previous Zika virus infection. Methods: Case–control study including 35 patients with Zika virus infection without evidence of neurological disease and 105 controls. Symptoms of autonomic dysfunction were assessed with the composite autonomic symptom scale 31 (COMPASS-31). Results: Patients with previous Zika virus infection had significantly higher COMPASS-31 score than controls regardless of age and sex (p = 0.007). The main drivers for the higher scores where orthostatic intolerance (p = 0.003), secretomotor (p = 0.04) and bladder symptoms (p  less than  0.001). Conclusion: Zika virus infection is associated with autonomic dysfunction. The mechanisms remain to be elucidated. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.